Spontaneous combustion of the organic mater in discards from the Witbank coalfield - R. M. Falcon (The Southern African Institute of Mining and Metallurgy, 1986)
The paper opens with a summary of the major factors responsible for spontaneous combustion in coal discards. These include heat arising from the oxidation of coal and pyrite, and from the weting of dry or oxidized coal and pyrite; and certain petrographic conditions leading to self-ignition of the coal such as low rank, the presence of a high proportion of reactive constituents, and the occurence of highly porous and botanicaly structured inertinite macerals, The analyses of 6 samples from 2 discard dumps in the Witbank coalfield are included, which show that, according to a three-grade classification of liability to spontaneous combustion, one dump is 'reasonably liable' and the other is 'most liable', It is pointed out that factors other than liability to self-ignition determine the possible utilization of such discards, and that the prevention of oxidation is of great importance if they are to be utilized and spontaneous combustion to be prevented,